Os conceitos de representação em schopenhauer - Carvalho, Diego Uchôa Souza (2013)
The present dissertation aims at exposing the representation concepts and their respective consequences regarded to Arthur Schopenhauer s world conception. The underlying representation concepts to Schopenhauerian philosophy answer to issues regarding to human knowledge and formulated since classical Antiquity, which justifies the plenty relevance of the theme. It is also very important the urgent need of underlining, in Schopenhauer thoughts, some subtle aspects of the general representation concept, to which the due importance wasn t given by many of those who study the matter. In the achieve of this, in a first moment, the text intends to delimit and expose the theoretical pressupositions which are indispensable to its right comprehension. Afterwards, it attempts to formulate the above-mentioned general concept. Thereafter, has the purpose of ordinating the specific representation concepts according to the Principle of Sufficient Reason. Finally, it has the objective of relating the preceeding ideas to the notion of Will as noumenon or thing-in-itself, besides explaning, based on this Will understanding, a new representation concept, which will be, this time, independent of the above-reffered principle.